Field-Free Orientation of CO Molecules by Femtosecond Two-Color Laser Fields - De, S.; Znakovskaya, I.; Ray, D.; Anis, F.; Johnson, Nora G.; Bocharova, I. A.; Magrakvelidze, M.; Esry, B. D.; Cocke, C. L.; Litvinyuk, I. V.; Kling, M. F. (My University, 2009)
We report the first experimental observation of nonadiabatic field-free orientation of a heteronuclear diatomic molecule (CO) induced by an intense two-color (800 and 400 nm) femtosecond laser field. We monitor orientation by measuring fragment ion angular distributions after Coulomb explosion with an 800 nm pulse. The orientation of the molecules is controlled by the relative phase of the two-color field. The results are compared to quantum mechanical rigid rotor calculations. The demonstrated method can be applied to study molecular frame dynamics under field-free conditions in conjunction with a variety of spectroscopy methods, such as high-harmonic generation, electron diffraction, and molecular frame photoelectron emission.